20. THE DECLINE OF TERRORIST GROUP: PENYEBAB MENURUNNYA AKSI TEROR KELOMPOK AL QAEDA TAHUN 2009 – 2013 - Fuad, Noor Azharul; Putranti, Ika Riswanti; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The number of incidents of terrorism continues to increase from year to year. Whenterrorism incidents in the world have been increased significantly, Al Qaeda has decreasedtheir acts of terror, especially in the year 2009 -2013. This study aims to determine thecause of the decline of terrorist attacks committed by Al Qaeda. This study use the theoryof the factors that are causing the decline of terrorism from Martha Crenshaw in theconcept of how terrorism decline. There are three factors that can cause the decline ofterrorism acts; first, the weakening of the result of the constant pressure from thegovernment, second, the decision of the members left the group then resulting in thedeployment of members, and the third is organizational destruction. This study use fieldobservations and interviews with former terrorists to obtain primary data. Then, theliterature study method was also performed to obtain supporting data secondary. The resultfrom this study is the factors that caused the decline of terrorist attacks by Al Qaeda in2009 - 2013 in accordance with the theory of Martha Crenshaw.